Breast prosthesis infection and pets: A case report and review of the literature. (2016) - Lenne, A.; Defourny, L.; Lafosse, A.; Martin, M.; Vandercam, B.; Berlière, M.; Lengelé, B.; Rodriguez-Villalobos, H.
Highlights: Underlining the relationship between P. multocida and breast prosthesis infection. Emphasizing the importance to avoid wound and close contact with pets. Informing patients about the risk of zoonotic infections in postoperative period. Abstract: Introduction: Pets are not always the human's best friends, particularly in the presence of comorbidities such as wounds. The following case report describes a Pasteurella multocida infection of a reconstructive breast implant due to a close contact between a cat and its owner. Presentation of case: A 33-year-old woman developed a breast implant infection 13 days after an immediate breast reconstruction following a mastectomy for a multifocal ductal carcinoma. The wound was explored surgically and the implant removed. Culture extracted from fluid around the prosthesis evidenced the presence of P. multocida, a Gram-negative coccobacillus which is present in the oral commensal flora of cats and dogs. Conclusion: In the case of breast infection, surgical revision – with or without removal of the implant – is required in order to carry out a meticulous intraoperative cleaning. Antibiotherapy is always necessary in such cases. Particularly when patients presenting comorbidities are concerned, the focus must be put on avoiding close contact of the wound with pets.